Harmonic Scalpel Hemorrhoidectomy Vs Milligan-Morgan Hemorrhoidectomy - Muhammad Umer Fayyaz, Muhammad Salman Shafique, Jahangir Sarwar Khan, Raheel Ahmad , Sheikh, Muhammad Umer Fayyaz, Muhammad Salman Shafique, Jahangir Sarwar Khan, Raheel Ahmad , Sheikh (Journal of Rawalpindi Medical College, 2017)
Background: To compare Harmonic Scalpel Hemorrhoidectomy (HSH) with classical Milligan Morgan Hemorrhoidectomy (MMH) in terms of operation time and post-operative pain to establish effectiveness of this novel procedure. Methods: A total of 62 patients planned for excision hemorrhoidecotmy were randomly selected into HSH and MMH groups. Mean operation time was calculated during surgery and pain at time of first defecation was recorded on visual analog scale (VAS). Results: Mean VAS after surgery at time of first defecation was 4.32 (SD 0.909) in HSH group and 6.97 (SD 1.426) in MMH group (p value <0.000). Mean Operation time in HSH group was 18.13 (SD 3.956) minutes and that of MMH group was 22.90 (SD 4.901) minutes (P value <0.000). Conclusion: Harmonic Scalpel Hemorrhoidectomy is better than Milligan Morgan hemorrhoidectomy